Defining and Measuring Inclusive Growth: Application to the Philippines - Ifzal Ali; Hyun H. Son (Asian Development Bank (ADB), 2007)
This study proposes an approach to defining and measuring inclusive growth using a new methodology to capture inclusive growth. In this context, the paper introduces the idea of a social opportunity function that is similar to a social welfare function. In this study, growth is defined as inclusive if it increases the social opportunity function, which depends on two factors: (i) average opportunities available to the population, and (ii) how opportunities are shared among the population. This idea is made operational by means of the opportunity curve, which has a one-to-one relationship with the social opportunity function. To complement the shortcoming of the opportunity curve particularly partial ranking, the study also develops the opportunity index to provide a complete ranking. The proposed methodologies are applied to the Philippines using its micro unit record household survey. Empirical applications analyze access to and equity of such opportunities as employment (total and also by gender); education; health; and basic infrastructure such as electricity, clean drinking water, and sanitation.
hdl:11540/1857
Keywords: 330; Entwicklungsindikator; Soziale Wohlfahrtsfunktion; Philippinen